PENGARUH MODAL INTELEKTUAL TERHADAP POTENSI PERTUMBUHAN PERUSAHAAN (Studi pada Perusahaan Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia) - Yunida Hary Wardany (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of this research is to investigate the influence of intellectual capital on the growth potential of companies. The intellectual capital is measured using VAIC™ method, which has three components, i.e. capital employed, measured using Value Added Capital Employed (VACA), human capital, measured using Value Added Human Capital (VAHU), and structural capital, measured using Structural Capital Value Added (STVA). The growth potential of companies is measured using Market to Book Value of Equity ratio (MVE/BVE). The population of this research is conventional banking companies with the total of 109 companies. Using purposive sampling methods, 95 conventional banking companies during 2013-2015 with specific criteria were selected. The data were analyzed through multiple linear regression analysis, and the hypotheses were tested using t test. The results of this research show that intellectual capital (VAIC) components that positively influence the growth potential of companies (Market to Book Value of Equity) is structural capital (STVA). It shows that Indonesian conventional banking companies use their structural capital, which is measured using STVA, to create added value that ultimately improve the company’s growth.Keywords: intellectual capital, the growth potential of company